2013
DOI: 10.1111/aogs.12035
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after bariatric surgery – a review of benefits and risks

Abstract: Pregnancy after bariatric surgery seems safe but larger studies matching or adjusting for body mass index are needed to improve the surveillance of these pregnancies and to assist in preventing adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 37 publications
2
54
2
6
Order By: Relevance
“…Recent studies on pregnant women after bariatric surgery with micronutrient deficiencies have proved no adverse perinatal outcomes. (36)(37)(38) In respect to obstetric risks, the remarkable fetomaternal benefits after bariatric surgery is the reduction of GDM and hypertension. ( 39) In our study the prevalence of preeclampsia, and GDM was 9%, 2.2% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on pregnant women after bariatric surgery with micronutrient deficiencies have proved no adverse perinatal outcomes. (36)(37)(38) In respect to obstetric risks, the remarkable fetomaternal benefits after bariatric surgery is the reduction of GDM and hypertension. ( 39) In our study the prevalence of preeclampsia, and GDM was 9%, 2.2% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the studies noted a decreased mean birth weight and a decreased rate of macrosomic birth weight, whereas 5 studies noted an increase in the proportion newborns who were small for gestational age (SGA) compared with normal or obese women. 21 It has also been reported that the risk of delivering an SGA baby varies with the type of surgery, with the greatest risk being associated with gastric bypass. 22 In summary, it appears that the risk of delivering a macrosomic newborn decreases following bariatric surgery but the risk of delivering an SGA baby increases.…”
Section: Birth Weightmentioning
confidence: 99%
“…This appears to be the case in women with weight loss induced by bariatric surgery for the outcomes gestational diabetes and macrosomia,3 but not for the outcome preterm birth where risks instead are increased 4. There is concern that bariatric surgery may cause fetal growth restriction2 3 5 6 through the resulting malabsorption and/or caloric restriction, depending on procedure type. There is also a lack of evidence for when pregnancy can be recommended after bariatric surgery.…”
Section: Contextmentioning
confidence: 99%
“…Several studies have shown increased risk for SGA and decreased risk for LGA in offspring to women with a history of bariatric surgery compared with deliveries to women matched for early pregnancy BMI 1 5 6. There are, however, fewer studies where matching has been done by presurgery BMI as in the current report from Chevrot and colleagues 3 7.…”
Section: Commentarymentioning
confidence: 99%